Smart Grid Security - Goel, Sanjay; Hong, Yuan.; Papakonstantinou, Vagelis; Kloza, Dariusz; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2015)
This book on smart grid security is meant for a broad audience from managers to technical experts. It highlights security challenges that are faced in the smart grid as we widely deploy it across the landscape. It starts with a brief overview of the smart grid and then discusses some of the reported attacks on the grid. It covers network threats, cyber physical threats, smart metering threats, as well as privacy issues in the smart grid. Along with the threats the book discusses the means to improve smart grid security and the standards that are emerging in the field. The second part of the book discusses the legal issues in smart grid implementations, particularly from a privacy (EU data protection) point of view.
Foreword -- Security Challenges in Smart Grid Implementation -- Legal Protection of Personal Data in Smart Grid and Smart Metering Systems from the EU Perspective. .
Keywords: Computer security; Systems and Data Security; European Law; Information Systems Applications (incl. Internet).; Energy Systems